The behavior of the composite multi-layer cylindrical shells subjected to blast load - Amir Esmaeel Khosravi (Iranian Society of Structrual Engineering (ISSE), 2017)
Today, with the increasing damages of explosion, it is of great significance to assess the performance of structures against such damages that established by explosive load. Accidental explosions exert great and intense dynamic forces to surrounding structures. Recently, composite shells have been used in structures to protect them against explosion which is due to its high resistance to volume ratio, flexibility and resistance to shock forces. Thus, it is essential to assess how structures protected by such materials behave against these forces. In this paper, we have used Abaqus software to analyze data pertaining the behavior of composite shells against explosive loads. We assessed the various parameters affecting the behavior of CRFP and E-Glass Epoxy and how they were affected by explosive load. Some of the parameters assessed include loading, curving rate, number of layers and size of interior angle. In practice, it is necessary to include openings in the composite shell, thus it is important to evaluate the effect of these openings on the behavior of the composite shell. The survey showed that use of the opening has fallen down shift. The reason for this phenomenon is reduction of area that effected by explosive load in composite shell